Answer:
![y(t)=2e^(3t)(2-5t)](https://img.qammunity.org/2020/formulas/mathematics/college/brbi7pmoeihepx251twpdtc7out4gslijf.png)
Explanation:
Let Y(s) be the Laplace transform Y=L{y(t)} of y(t)
Applying the Laplace transform to both sides of the differential equation and using the linearity of the transform, we get
L{y'' - 6y' + 9y} = L{0} = 0
(*) L{y''} - 6L{y'} + 9L{y} = 0 ; y(0)=4, y′(0)=2
Using the theorem of the Laplace transform for derivatives, we know that:
![\large\bf L\left\{y''\right\}=s^2Y(s)-sy(0)-y'(0)\\\\L\left\{y'\right\}=sY(s)-y(0)](https://img.qammunity.org/2020/formulas/mathematics/college/y167d7ccvsuubbjk1nv8i5vo12awos88ep.png)
Replacing the initial values y(0)=4, y′(0)=2 we obtain
![\large\bf L\left\{y''\right\}=s^2Y(s)-4s-2\\\\L\left\{y'\right\}=sY(s)-4](https://img.qammunity.org/2020/formulas/mathematics/college/7z8jo9979qws3qo1iuq7qh9aqh6vjes4rn.png)
and our differential equation (*) gets transformed in the algebraic equation
![\large\bf s^2Y(s)-4s-2-6(sY(s)-4)+9Y(s)=0](https://img.qammunity.org/2020/formulas/mathematics/college/etdkm4b6m2sr565bp7zm8zfyws06uym0i1.png)
Solving for Y(s) we get
![\large\bf s^2Y(s)-4s-2-6(sY(s)-4)+9Y(s)=0\Rightarrow (s^2-6s+9)Y(s)-4s+22=0\Rightarrow\\\\\Rightarrow Y(s)=(4s-22)/(s^2-6s+9)](https://img.qammunity.org/2020/formulas/mathematics/college/k82ucu12h2zrvsbvjuo3rwm1pjobtma8ec.png)
Now, we brake down the rational expression of Y(s) into partial fractions
![\large\bf (4s-22)/(s^2-6s+9)=(4s-22)/((s-3)^2)=(A)/(s-3)+(B)/((s-3)^2)](https://img.qammunity.org/2020/formulas/mathematics/college/eggpaakscr06m5cba71xlktgwir5ng5lkp.png)
The numerator of the addition at the right must be equal to 4s-22, so
A(s - 3) + B = 4s - 22
As - 3A + B = 4s - 22
we deduct from here
A = 4 and -3A + B = -22, so
A = 4 and B = -22 + 12 = -10
It means that
![\large\bf (4s-22)/(s^2-6s+9)=(4)/(s-3)-(10)/((s-3)^2)](https://img.qammunity.org/2020/formulas/mathematics/college/jpdsz6tb5vzpglnrayuy3sj38urw2xe9d1.png)
and
![\large\bf Y(s)=(4)/(s-3)-(10)/((s-3)^2)](https://img.qammunity.org/2020/formulas/mathematics/college/v496ewl3tjzmc3hw58i93v8gxllqpcjw89.png)
By taking the inverse Laplace transform on both sides and using the linearity of the inverse:
![\large\bf y(t)=L^(-1)\left\{Y(s)\right\}=4L^(-1)\left\{(1)/(s-3)\right\}-10L^(-1)\left\{(1)/((s-3)^2)\right\}](https://img.qammunity.org/2020/formulas/mathematics/college/fpk85hvf3pu2dwvwteg17bqo9t95fubsbm.png)
we know that
![\large\bf L^(-1)\left\{(1)/(s-3)\right\}=e^(3t)](https://img.qammunity.org/2020/formulas/mathematics/college/7akj202lofi8848s5useyaibnhbdzt4mqb.png)
and for the first translation property of the inverse Laplace transform
![\large\bf L^(-1)\left\{(1)/((s-3)^2)\right\}=e^(3t)L^(-1)\left\{(1)/(s^2)\right\}=e^(3t)t=te^(3t)](https://img.qammunity.org/2020/formulas/mathematics/college/2bfy9d0pa7zehtv15ahk4sm399oxmaxv1g.png)
and the solution of our differential equation is
![\large\bf y(t)=L^(-1)\left\{Y(s)\right\}=4L^(-1)\left\{(1)/(s-3)\right\}-10L^(-1)\left\{(1)/((s-3)^2)\right\}=\\\\4e^(3t)-10te^(3t)=2e^(3t)(2-5t)\\\\\boxed{y(t)=2e^(3t)(2-5t)}](https://img.qammunity.org/2020/formulas/mathematics/college/be2ky8zerv2r2ekaioo7s050h8b46p0a9j.png)